Sonhos diurnos em meio aos destroços do presente: o movimento Tarifa Zero e a luta pelo direito ao transporte em Belo Horizonte - Igor Thiago Moreira Oliveira (2017)
This thesis seeks to describe and understand the struggle for the right to transport from 2013 onwards, carried out by the Tarifa Zero movement in the city of Belo Horizonte. The Tarifa Zero movement has its history directly related to the great protests that marked the Brazilian society during the holding of the Confederations Cup in June 2013. The investigation on the meanings of the action of the Tarifa Zero movement started from a wider context: that of the intersection between the struggle for social rights, the field of political experiences and the horizon of future expectations built by Brazilian society throughout its recent democratic history. The analysis then sought to emphasize the constitutive processes and characteristics of this movement in order to understand what it has to say about the social movements carried out by young people in the contemporary world and what they have to say about the changes in society Brazilian contemporary art. The research was developed from an engaged ethnography, the militant copesquisa (CAVA, 2013; ROGGERO, 2013). This theoretical-methodological perspective brought about an approximation between researcher and the subjects of the investigation that allowed to understand and to perceive the dilemmas, obstacles, risks and powers of the political action of the young participants of the movement. In a historical moment marked by uncertain and negative expectations about the future, in Brazil and in the world, the research brings elements for dialogue about the possibilities and limits of contemporary political action carried out by young urban activists